2021
DOI: 10.1007/s10826-021-02102-2
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Mediated Communication and Child/Adolescent Friendship Quality after Residential Relocation

Abstract: The experience of residential relocation can affect children and adolescents in various ways. It often affects their close social relationships, and this is especially true when these individuals are no longer in close proximity to their family members and friends. Although face-to-face communication may be limited after relocation, computer-mediated communication can assist in maintaining and developing existing relationships. It may even help individuals initiate new social relationships. In the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…They concluded that emotional communication online and offline is surprisingly similar, and if differences are found they show more frequent and explicit emotional communication (especially negative emotions) in CMC than in F2F. Yet, few studies have systematically examined CMC used by children and youth (Wendt & Langmeyer, 2021).…”
Section: Second Phase Of the Study: Exploring The Content And The Emo...mentioning
confidence: 99%
“…They concluded that emotional communication online and offline is surprisingly similar, and if differences are found they show more frequent and explicit emotional communication (especially negative emotions) in CMC than in F2F. Yet, few studies have systematically examined CMC used by children and youth (Wendt & Langmeyer, 2021).…”
Section: Second Phase Of the Study: Exploring The Content And The Emo...mentioning
confidence: 99%
“…Teachers merely mentioned the use of group work (Wang et al, 2021), the integration of social media (Nowell, 2014), and that students find time outside of class to connect (Page et al, 2021a). Youth generally spend more time online, and view the environment as conducive for maintaining and developing friendships (Mittmann et al, 2022;Wendt & Langmeyer, 2021). Future studies should explore the adoption of strategies suggested for enhancing online peer networks and support in tertiary education, such as implementing collaborative learning and creating formal peer mentoring programs (Wissing et al, 2022).…”
Section: Practical Approachesmentioning
confidence: 99%
“…Tiktok usage activities are required to use the internet (Evelina et al, 2021). CMC theory (Computer Mediated Communication) is a new set of expectations about the developing community around computer-mediated communication (Wendt & Langmeyer, 2021). The core idea is that a "virtual community" can be formed by any number of individuals via the internet on the basis of their own choice or in response to a stimulus (Burton & McQuail, 2021).…”
Section: Introductionmentioning
confidence: 99%